Faktor-faktor yang Memengaruhi Produksi dan Efektivitas Panen pada Kakao Mulia - Thifany, Ariny Jihan; Santosa, Edi; Khumaida, Nurul (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2020)
Low productivity of cocoa (Theobroma cacao L.) in Indonesia is caused by various factors such as improper harvesting practice. The research studied growth, development, and distribution of pod on two edel cocoa clones (DR 2 and DRC 16) and to evaluate factors affecting production and harvesting effectivity. The study was carried out at cocoa farm located at Renteng Plantation, Jember, East Java, Indonesia in January-May 2019. Pod growth, distribution, and disease incidents were evaluated on the stem 0-200 cm from soil level. The results showed that harvested pod met 73.51% of the standard quality. DR 2 and DRC 16 matured about 21-24 and 19-22 weeks after anthesis, respectively. Pods distributed predominantly at 151-200 cm above soil surface, and number of pod increased from lower to higher stem. Cocoa production was affected by clone, fruit position on the stem height, pest and disease infections, and harvester’s age and their height. In order to increase cocoa production, it is important to increase harvesting effectivity by managing fruit position such as maintaining tree height to fit with harvester’s age and height.